Corrosion Behaviour Of Steel For Simulated Concete In Choride Aqueous Solution - Chang , Weng Soon (UTeM, 2008)
Steel reinforced concrete is probably the most extensively used construction material in the world. However, many cases of structural failure have occurred during recent years especially for those structures that are exposed to marine environment such as harbour structures and bridge structures. Structural failures are mainly due to the steel reinforcement corrosion. The objective of this study has been conducted to look into the effect of different concentration of chloride content on corrosion rate in steel reinforced concrete. The second objective is to compare and study the morphology of reinforced steel before and after corrosion based on difference concentration of chloride in concrete. The reinforced steel bar used in this study was based on commercially available which obtained from Ann Joo Steel Berhad. Four steel reinforced concrete specimens were manufactured with cement/sand/water ratio of 1:3:0.5 by weight. Then, each of the specimens was subjected to concentrations of sodium chloride solution with the percentage of 1%, 3%, 5%, and 7% by weight for reveal the relationship between chloride ion and corrosion rate. The morphology of reinforced steels is compared and analysis. The study is shown that the corrosion rate of reinforced steel bar is directly proportional to the chloride concentration. The corrosion products on reinforced steel bar also increase with the chloride concentration .Some pits are found on the reinforced steel .Finally, the potential of cost saving and life saving is high via understanding the corrosion behaviour and problem of steel reinforced concrete before tragedy occurred.